Polypragmasy at treatment of H. pylori infection in patients with concomitant diseases of other organs and systems. How to prevent side effects related to drug interactions? - S. G. Burkov; N. V. Shornikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. Issues of drug interaction, side effects development at patients with combined diseases, requiring eradication treatment, are taken into account.Original positions. Being based on literature data and own experience, authors demonstrated, that drug interactions are observed in vast majority of cases at simultaneous prescription of five drugs and more. As eradication therapy implicates addition to treatment of at least 3 pharmaceuticals of which antibiotics are strictly specified, it is extremely desirable to choose proton pump inhibitor (PPI) with lower affinity to cytochrome Р450. Pantoprazole conform to these requirements, and surpasses all other PPIs in this respect.Conclusion. Authors believe, taking into account available data on drug interactions, that at patients with multiple morbidity pantoprazole is preferable to other antisecretory agents.